2014
DOI: 10.2967/jnumed.113.129221
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Translational PET/MR Imaging

Abstract: Combined PET and MR imaging (PET/MR imaging) has progressed tremendously in recent years. The focus of current research has shifted from technologic challenges to the application of this new multimodal imaging technology in the areas of oncology, cardiology, neurology, and infectious diseases. This article reviews studies in preclinical and clinical translation. The common theme of these initial results is the complementary nature of combined PET/MR imaging that often provides additional insights into biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 74 publications
1
42
0
1
Order By: Relevance
“…48 In the present study, no attempt was made to compute standardized uptake values (SUVs) of tracers. By normalizing the tissue concentration to the administered dose or the subject's weight, it is thought that SUVs improve the precision of PET quantification.…”
Section: Quantitative Vs Relative Pet Imagingmentioning
confidence: 96%
“…48 In the present study, no attempt was made to compute standardized uptake values (SUVs) of tracers. By normalizing the tissue concentration to the administered dose or the subject's weight, it is thought that SUVs improve the precision of PET quantification.…”
Section: Quantitative Vs Relative Pet Imagingmentioning
confidence: 96%
“…37 In the case of pressure overload, we found in studies using the SHR an increased reliance on carbohydrate oxidation in an attempt to maintain contractile function with a decline in fatty acid and oxygen utilization. 26 Additionally, in PET/MRI studies of the normal Lewis rat, we found that glucose metabolic rate was inversely proportional to tissue work 38 indicating that a more efficient metabolic substrate such as fatty acid would more likely be proportional to increased work. These results are exciting and provide an impetuous to study cardiac efficiency in relation to glucose and fatty acid metabolism in health and disease.…”
mentioning
confidence: 82%
“…Among the promising ligands, Pittsburgh compound B (PiB), developed by Mathis et al (1) and Klunk et al (2), is one well-known example. In cooperation with Långström and his group in Uppsala, PiB was labeled with 11 C and applied clinically (3). The tracer was soon used in many other academic centers and initiated such continuous interest that 3 compounds-18 F-florbetapir, 18 F-flutemetamol, and 18 F-florbetaben-obtained approval by the Food and Drug Administration for regular clinical application.…”
Section: To the Editormentioning
confidence: 99%
“…PET imaging of such plaques was successfully demonstrated by Maetzler et al with 11 C-PiB (6). In general, the existence of plaques in muscles is known as inclusion body myositis (IBM), and the PET findings indicated amyloid b deposition.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation